Management of challenging immune-related gastrointestinal adverse events associated with immune checkpoint inhibitors. (6th September 2018) - Hamamoto, Yasuo; Shin, Natalya; Hoshino, Tomohiro; Kanai, Takanori
Immune-related gastrointestinal toxicities (irGI) are well-known adverse events (AEs) with immune checkpoint inhibitors. The aim of this review was to present clinical data from 82 cases to provide information to clinicians who face real-world challenges among their patients with irGI AEs. The findings of this review support the use of the current management guidelines. By analyzing the treatment courses and outcomes of all cases identified, our review recommends that recurrent cases be treated carefully regardless of the grade of diarrhea at the onset of events. Earlier gastroenterology consultation and computed tomography/endoscopy diagnosis are essential, especially when an irGI AE recurs or worsens during steroid tapering. We would also suggest earlier decision to add immunosuppressant agents, particularly for recurrent cases.